From the optic tectum to the primary visual cortex: migration through evolution of the saliency map for exogenous attentional guidance. (October 2016) - Zhaoping, Li
Highlights: A saliency map in the primary visual cortex for primates. A saliency map in the optic tectum for archer fish. Through evolution, the saliency map migrated from the optic tectum to the primary visual cortex. Abstract : Recent data have supported the hypothesis that, in primates, the primary visual cortex (V1) creates a saliency map from visual input. The exogenous guidance of attention is then realized by means of monosynaptic projections to the superior colliculus, which can select the most salient location as the target of a gaze shift. V1 is less prominent, or is even absent in lower vertebrates such as fish; whereas the superior colliculus, called optic tectum in lower vertebrates, also receives retinal input. I review the literature and propose that the saliency map has migrated from the tectum to V1 over evolution. In addition, attentional benefits manifested as cueing effects in humans should also be present in lower vertebrates.